Impact of Backbone fluorination on -conjugated polymers in organic photovoltaic devices: a review - Leclerc, Nicolas; Chávez, Patricia; Ibraikulov, Olzhas A.; Heiser, Thomas; Lévêque, Patrick (Polymers, 2016)
Solution-processed bulk heterojunction solar cells have experienced a remarkable acceleration in performances in the last two decades, reaching power conversion efficiencies above 10%. This impressive progress is the outcome of a simultaneous development of more advanced device architectures and of optimized semiconducting polymers. Several chemical approaches have been developed to fine-tune the optoelectronics and structural polymer parameters required to reach high efficiencies. Fluorination of the conjugated polymer backbone has appeared recently to be an especially promising approach for the development of efficient semiconducting polymers. As a matter of fact, most currently best-performing semiconducting polymers are using fluorine atoms in their conjugated backbone. In this review, we attempt to give an up-to-date overview of the latest results achieved on fluorinated polymers for solar cells and to highlight general polymer properties’ evolution trends related to the fluorination of their conjugated backbone.
Keywords: fluorine; organic photovoltaics; conjugated polymer; optoelectronic; Research Subject Categories::NATURAL SCIENCES::Physics::Nuclear physics::Middle energy physics